2021
DOI: 10.1021/acs.analchem.0c04974
|View full text |Cite
|
Sign up to set email alerts
|

Microdroplet Ultrafast Reactions Speed Antibody Characterization

Abstract: Recently, microdroplet reactions have aroused much interest because the microdroplet provides a unique medium where organic reactions could be accelerated by a factor of 103 or more. However, microdroplet reactions of proteins have been rarely studied. We report the occurrence of multiple-step reactions of a large protein, specifically, the digestion, reduction, and deglycosylation of an intact antibody, which can take place in microseconds with high reaction yields in aqueous microdroplets at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“…Previous studies have shown increased droplet reactivity with increased flight distance due to solvent evaporation, which leads to concentration and surface effects. Similar observations have recently been made with the contained-ES apparatus even at short analytical spray distances (<5 mm), , making it possible to accurately examine the kinetics of lipase hydrolysis using known droplet velocities to convert the cavity length to reaction time. This required important control experiments to enable correct interpretation of data.…”
Section: Resultssupporting
confidence: 57%
“…Previous studies have shown increased droplet reactivity with increased flight distance due to solvent evaporation, which leads to concentration and surface effects. Similar observations have recently been made with the contained-ES apparatus even at short analytical spray distances (<5 mm), , making it possible to accurately examine the kinetics of lipase hydrolysis using known droplet velocities to convert the cavity length to reaction time. This required important control experiments to enable correct interpretation of data.…”
Section: Resultssupporting
confidence: 57%
“…; Wei et al, 2020 , 2022 ; Cao et al, 2020 ; Kuai et al, 2021 ; Vannoy et al, 2021 ; Zheng et al, 2021 ), and the unique properties of the reaction environment ( Li et al, 2014 ; Lee et al, 2019a , 2019b ; Gao et al, 2019 ; Huang et al, 2021 ; Wang et al, 2021 ; Gong et al, 2022 ; Qiu et al, 2022 ). These features give rise to numerous applications ( Wei et al, 2017 ; Yan et al, 2018 ; Zhu et al, 2019 ; Nie et al, 2020 ; Li Z. et al, 2021 ; Gunawardena et al, 2021 ; Yan, 2021 ; Zhang, 2021 ). Reaction acceleration is firmly attributed to the reactions at the solution/air interface ( Yan et al, 2016 ; Lee et al, 2019b ; Wei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Figure 1C, the droplet reaction with or without charge may be conducted offline and the products were collected and injected onto MS [8,42]. This is particularly useful for sample preparation or large-scale synthesis.…”
Section: Offline Reactionmentioning
confidence: 99%
“…Microdroplet chemistry has been widely studied using MS mainly via ESI and desorption electrospray ionization (DESI) which are soft ionization methods of MS to transform the analyte molecules in condensed phase to gas phase before entering the MS inlet. Pioneered studies by Cooks [5][6][7] and Zare [8][9][10], noted that when reagents are confined in a microdroplet, various chemical reactions, such as redox reactions [8,[11][12][13][14][15][16], enzyme digestion [8,9], acid-/base-catalyzed reactions [17,18], can occur in microseconds to milliseconds, which is considered 10 5 × faster than the reaction in the bulk. Beyond mechanistic studies, amazing reactions in microdroplets was used in organic synthesis [11,19], chemical derivatization [20], protein folding/unfolding [21], and protein digestion [8,9], which can greatly enhance the capability of application fields including green and sustainable synthesis [11], high-throughput screening [6,12], protein sequencing [8,9], and protein characterization [9].…”
Section: Introductionmentioning
confidence: 99%